A multi-levels analysis to evaluate the toxicity of microplastics on aquatic insects: A case study with damselfly larvae (Ischnura elegans) - Sun, Lin; Cheng, Zhongyan; Wang, Mei; Wei, Chao; Liu, Haoyu; Yang, Yuxia (Ecotoxicology and environmental safety, 2025)
Microplastic (MP) pollution prevalent in freshwater environments and jeopardizes the organisms living there. Dozens of studies have been conducted to investigate the harmful effects of microplastics on organisms. However, the most diverse and sensitive aquatic insects are often overlooked, also there is a lack of a comprehensive research exploring the toxicity of microplastics. Here, taking the damselfly larvae (Ischnura elegans) as the subject, we investigated the effects of different concentration levels of polystyrene microplastics (PS MPs) on their physiological characters, behavioristics, metabolomics and transcriptomics, as well as gut microbiome. The results showed that the PS MPs had no significant effects on the body weight and survival rate, but led to behavioral inhibition. Furthermore, expression levels of some metabolites altered, such as nicotinic acid, fumaric acid, and stearic acid. Meanwhile, the pathways related to oxidative phosphorylation and carbon metabolism were upregulated at the transcriptomic level. Moreover, there was a modification of the gut microbial community, with an increase in species richness but a shift towards potentially harmful bacteria. Our findings suggested that exposure to PS MPs affected the overall health of damselfly larvae. Therefore, effective management of MPs to minimize their environmental input is crucial in reducing health risks to aquatic organisms. [Display omitted] •PS MPs had no significant effects on the body weight and survival rate of damselfly larvae.•The activity and movement tendency decreased with the increase of PS MPs concentration.•Expression levels of some metabolites altered, such as nicotinic acid, fumaric acid, and stearic acid.•The pathways related to oxidative phosphorylation and carbon metabolism were upregulated.•The species richness of gut microbes increased significantly, and the composition altered.